Improved autonomous current‐fed push–pull resonant inverter. Issue 8 (1st August 2014) - Abdolkhani, Ali; Hu, Aiguo Patrick
Abstract : This study presents an improved autonomous current‐fed push–pull resonant inverter with integrated driving power from the input DC source and zero voltage switching (ZVS) signals from the resonant tank. Unlike the conventional current‐fed inverters, the new inverter can increase the system operating frequency up to MHz while maintaining ZVS operation. Moreover, the primary resonant capacitance can be eliminated by advantageously utilising the output capacitances of the switches for resonance. Both simulation and practical results have demonstrated that the proposed inverter is able to generate high quality resonant currents from kHz to 10 MHz for inductive power transfer, induction heating and other applications where high‐frequency currents or voltages are required.